2022
DOI: 10.1007/s00253-021-11740-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virulence determinants and phylogenetic background of multiple and extensively drug resistant Escherichia coli isolated from different clinical sources in Egypt

Abstract: Escherichia coli is a multifaceted microbe since some are commensals, normally inhabiting the gut of both humans and animals while others are pathogenic responsible for a wide range of intestinal and extra-intestinal infections. It is one of the leading causes of septicemia, neonatal meningitis, urinary tract infections (UTIs), cystitis, pyelonephritis, and traveler’s diarrhea. The present study aims to survey the distribution and unravel the association of phylotypes, virulence determinants, and antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 95 publications
(138 reference statements)
2
8
0
Order By: Relevance
“…Such a high distribution of the fimH gene was also confirmed in studies conducted in Ethiopia, Romania, Mongolia, Iran, Mexico, and China [ 13 , 41 , 42 , 43 , 44 , 45 , 46 ], which may indicate a key role of this factor in the development of UTI. The percentage of other VFs (Sfa, PapC, HlyA, CNF1) that characterize the strains in the studied collection is on par with another study conducted in Poland [ 47 ], while in other countries, the share of these factors varies [ 13 , 48 , 49 , 50 , 51 , 52 ]. A high percentage of sequences encoding SitA and Aer characterized the UPEC studied, and this observation is in line with the results obtained in other studies [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 52%
“…Such a high distribution of the fimH gene was also confirmed in studies conducted in Ethiopia, Romania, Mongolia, Iran, Mexico, and China [ 13 , 41 , 42 , 43 , 44 , 45 , 46 ], which may indicate a key role of this factor in the development of UTI. The percentage of other VFs (Sfa, PapC, HlyA, CNF1) that characterize the strains in the studied collection is on par with another study conducted in Poland [ 47 ], while in other countries, the share of these factors varies [ 13 , 48 , 49 , 50 , 51 , 52 ]. A high percentage of sequences encoding SitA and Aer characterized the UPEC studied, and this observation is in line with the results obtained in other studies [ 53 , 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 52%
“…However, they demonstrated complete resistance to AMP, 60% resistance to AMX-C acid, and significant resistance to cephalosporins, GEN, and AMK. According to other studies, ESBL-producing bacteria are known to produce a significant level of antibiotic resistance in E. coli [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study from Himachal Pradesh (India) also observed no signi cant difference between MDR and MDS P. aeruginosa clinical isolates for expression of virulence traits [15]. Other studies have also reported no signi cant relation between expression of virulence traits and multi drug resistant phenotype [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%